Evaluation of electrocardiographic P wave parameters in predicting long-term atrial fibrillation in patients with acute ischemic stroke - Çinar, Tufan; Hayiroğlu, Mert İlker; Selçuk, Murat; Cinier, Göksel; Çiçek, Vedat; Doğan, Selami; Kiliç, Şahhan; Asal, Süha; Atmaca, Murat Mert; Orhan, Ahmet Lütfullah (Arquivos de Neuro-Psiquiatria, 2022)
Background Electrocardiographic parameters, such as P wave peak time (PWPT), P wave duration (PWD), and P wave amplitude in lead DI, have been utilized to assess left atrial anomalies linked to the development of atrial fibrillation (AF) in different cohort settings.Objective To compare electrocardiographic parameters, such as P waves, in predicting long-term AF risk in acute ischemic stroke cases.Methods The data of 231 consecutive acute ischemic stroke cases were retrospectively collected. Two independent cardiologists interpreted the electrocardiography recordings for PWPT, PWD, and P wave amplitude in lead DI. The median follow-up study period was 16 (interquartile range [IQR]: 11–24) months.Results In total, AF was detected in 43 (18.6%) cases. All studied P wave parameters were found to be statistically significant in cases with AF. Based on multivariable logistic regression analysis, dementia, left atrium volume index, PWD (razão de chances [RC]: 1.11; 95% confidence interval [CI]: 1.058–1.184; p = 0.003), PWPT in lead DII (RC: 1.030; 95%CI: 1.010–1.050; p = 0.003), and advanced interatrial block morphology were independent predictors of long-term AF. P wave duration had the highest area under the curve value, sensitivity, and specificity for long-term AF in such cases compared with the other P wave parameters.Conclusions Our head-to-head comparison of well-known P wave parameters demonstrated that PWD might be the most useful P wave parameter for long-term AF in acute ischemic stroke cases.
Keywords: p Wave; Reference Parameters; Electrocardiography; Ischemic Stroke